Mecanismo de defensa del erizo europeo (Erinaceus europaeus) - Melero Asensio, Mar; Rubio Guerri, Consuelo; Ruiz-lopera Zorrilla, Silvia (Revista Complutense de Ciencias Veterinarias, 2007)
Sin resumen